Chronic loss of noradrenergic tone produces β‐arrestin2‐mediated cocaine hypersensitivity and alters cellular D2 responses in the nucleus accumbens. (13th August 2014) - Gaval‐Cruz, Meriem; Goertz, Richard B.; Puttick, Daniel J.; Bowles, Dawn E.; Meyer, Rebecca C.; Hall, Randy A.; Ko, Daijin; Paladini, Carlos A.; Weinshenker, David
Abstract: Cocaine blocks plasma membrane monoamine transporters and increases extracellular levels of dopamine (DA), norepinephrine (NE) and serotonin (5‐HT). The addictive properties of cocaine are mediated primarily by DA, while NE and 5‐HT play modulatory roles. Chronic inhibition of dopamine β‐hydroxylase (DBH), which converts DA to NE, increases the aversive effects of cocaine and reduces cocaine use in humans, and produces behavioral hypersensitivity to cocaine and D2 agonism in rodents, but the underlying mechanism is unknown. We found a decrease in β‐arrestin2 (βArr2) in the nucleus accumbens (NAc) following chronic genetic or pharmacological DBH inhibition, and overexpression of βArr2 in the NAc normalized cocaine‐induced locomotion in DBH knockout ( D bh − / −) mice. The D2/3 agonist quinpirole decreased excitability in NAc medium spiny neurons (MSNs) from control, but not D bh − / − animals, where instead there was a trend for an excitatory effect. The Gαi inhibitor NF023 abolished the quinpirole‐induced decrease in excitability in control MSNs, but had no effect in D bh − / − MSNs, whereas the Gαs inhibitor NF449 restored the ability of quinpirole to decrease excitability in D bh − / − MSNs, but had no effect in control MSNs. These results suggest that chronic loss of noradrenergic tone alters behavioral responses to cocaine via decreases in βArr2 and cellular responses to D2/D3 activation, potentially via changes in D2‐like receptor G‐protein coupling in NAc MSNs.